School of Russian as a Foreign Language - N. D. Afanasieva (Vestnik MGIMO-Universiteta, 2014)
Teaching Russian as a foreign language at MGIMO began almost simultaneously with the creation of the university itself. At its core is the interdepartmental chair. Department of Russian language for foreign students is one of the leading departments of the university.